In vitro phosphorylation and purification of a nonstructural protein of bluetongue virus with affinity for single-stranded RNA. - Huismans, H (1987)
A phosphorylated, nonstructural protein of bluetongue virus, NS2, is synthesized throughout the replication cycle in comparatively large amounts. The protein was detected in both the soluble and particulate fraction of the cytoplasm of infected cells. The particulate NS2 could be solubilized in 0.5 M NaCl. It was found that NS2 in the particulate fraction and immunoprecipitates of NS2 from the soluble protein fraction could be phosphorylated in vitro. It is not known whether the kinase involved is of cellular or viral origin, but after purification of NS2 by affinity chromatography on poly(U)-Sepharose it could still by phosphorylated in vitro without the addition of exogenous protein kinase. The affinity of NS2 for nucleic acid was also investigated. The protein was found to bind to single-stranded RNA. In the presence of purified bluetongue virus mRNA, NS2 formed a complex with an estimated S value of about 22S.